1993
DOI: 10.1002/rem.3440030306
|View full text |Cite
|
Sign up to set email alerts
|

Soil washing for volume reduction of radioactively contaminated soils

Abstract: Micbael C Eagle is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In every instance, clean-up requires knowledge of the mechanical properties of the contaminated sand and the level of crude oil contamination to determine the appropriate remediation method in terms of cost and efficiency. Eagle, et al [ 11 ] indicated that soil washing presents the cheapest remediation method in terms of capital cost, but this method requires up to 23 months. Other methods include vitrification, biological oxidation, chemical oxidation, soil stabilization and encapsulation with cement.…”
Section: Introductionmentioning
confidence: 99%
“…In every instance, clean-up requires knowledge of the mechanical properties of the contaminated sand and the level of crude oil contamination to determine the appropriate remediation method in terms of cost and efficiency. Eagle, et al [ 11 ] indicated that soil washing presents the cheapest remediation method in terms of capital cost, but this method requires up to 23 months. Other methods include vitrification, biological oxidation, chemical oxidation, soil stabilization and encapsulation with cement.…”
Section: Introductionmentioning
confidence: 99%